2019
DOI: 10.1111/opn.12290
|View full text |Cite
|
Sign up to set email alerts
|

“All for One” experiences of interprofessional team members caring for older adults: A metasynthesis

Abstract: Background: There is some evidence that healthcare professionals prefer an interprofessional approach to care and this approach is of particular importance to older people due to their complex needs and multitude of chronic conditions.Objective: This metasynthesis aimed to synthesise and unearth new understandings of the experiences of interprofessional team members that are caring for older people from a variety of qualitative studies.Design: This review is designed as a metasynthesis based on the method put … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, the studies identified covered a large, diverse geographical spread, income settings, different configurations of disease programmes being integrated and a variety of integration implementation strategies and appear to reflect both the homogeneity and similar implementation considerations noted in other reviews [ 9 , 21 , 26 , 52 , 54 56 ]. We received feedback from WHO working group on the draft findings which was an opportunity to check the relevance and applicability of the findings.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Nevertheless, the studies identified covered a large, diverse geographical spread, income settings, different configurations of disease programmes being integrated and a variety of integration implementation strategies and appear to reflect both the homogeneity and similar implementation considerations noted in other reviews [ 9 , 21 , 26 , 52 , 54 56 ]. We received feedback from WHO working group on the draft findings which was an opportunity to check the relevance and applicability of the findings.…”
Section: Discussionmentioning
confidence: 74%
“…A review on continuity of chronic care for in remote rural Australia highlighted similar resource issues, and stressed the importance of skilled staff which local cultural knowledge [ 55 ]. In a review of experiences of interprofessional team members caring for older adults, the authors note as we did in our review, the importance of the relational elements of building a multi-disciplinary team and change management [ 56 ]. Their review provides further insights on the inevitable stressors, tensions, territoriality, and unequal power dynamics associated with interprofessional team dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, these IPE opportunities further facilitate effective IPCP. Findings from metasyntheses by Johnson et al (2020) and Montano (2019) support the need for interprofessional training for clinicians, as traditional training models perpetuate learning and practicing in silos. However, it is clear from the theme The “C” in IPCP , even more than IPE, collaboration is a key facilitator to effective IPCP and it is essential that professionals have a strong desire to collaborate (Malcolm, Shellman, Elwell, et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…The dependence on inter-organizational collaboration in emergency situations, and the lack of structured collaboration between the EMS and the municipal home care organization put older persons’ well-being at risk. Research on inter-professional collaboration stresses the need for clarified roles, shared goals, respectful communication, and recognition of interdependence for collaboration to be successful in the care of older persons (Montano, 2019 ). The lack of clearly defined roles for care personnel within municipal home care have been pointed out in previous research (Bing-Jonsson et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%